Afectos y violencias en la cultura latinoamericana - Dhondt, Reindert; Mandolessi, Silvana; Zícari, Martín (Nexos y Diferencias. Estudios de la Cultura de América Latina, 2022)
This volume presents an analysis of the relationship between violence and affection in Latin American culture. From an interdisciplinary perspective, the contributions that comprise it address a wide spectrum of cultural productions, including literature, film, photography, installations, and performances. The volume offers an overview of the trajectory and impact of the affective turn in the region, questioning the specificity that affective theory acquires in Latin America, while exploring the mutations of the concept of violence in the contemporary panorama. The political potential of ugly affects, the affective effectiveness of works of art to mobilize the viewer, the exploration of uncomfortable affective positions or affect as a deterritorialized form in contemporary cinema are some of the intersections between affections and violence that the book investigates